Analisis Penyalahgunaan Obat Tramadol Pada Kalangan Remaja - Valya Ulitamanda; Edy Setyawan (Hukum, 2025)
Tramadol is a prescription opioid analgesic with legitimate medical uses but a significant potential for misuse, dependence, intoxication, and harmful interactions when consumed without medical supervision. This study analyzes the risk factors, health and psychosocial impacts, and legal framework governing tramadol misuse among adolescents in Indonesia. It employs normative legal research combined with a literature-review approach using statutory, conceptual, and socio-legal perspectives. Primary legal materials include Law Number 17 of 2023 on Health, the Indonesian Food and Drug Authority regulations on frequently misused medicines, and relevant pharmaceutical-control provisions. Secondary materials consist of scholarly books and journal articles on adolescent deviance, family counseling, peer influence, psychological consequences, and tramadol misuse. The materials are qualitatively analyzed through classification, comparison, and legal interpretation. The findings show that adolescent tramadol misuse is driven by peer pressure, easy access, curiosity, family conflict, stress, weak supervision, and the normalization of drug use within deviant subcultures. Its effects may include dependence, mood changes, impaired judgment, aggression, school disengagement, social isolation, and serious physical risks. Legally, tramadol is not automatically classified as a narcotic under the Narcotics Law; it is regulated as a prescription medicine and as a frequently misused medicine requiring strict pharmaceutical control. Therefore, users cannot simply be charged under narcotics provisions solely because they possess or consume tramadol. Criminal liability primarily concerns unlawful production, distribution, sale, or circulation of pharmaceutical products, while adolescents who misuse tramadol require health-oriented, child-protection, counseling, family, and restorative interventions. Effective policy must combine supply control, pharmacy supervision, online-market enforcement, school-based prevention, family counseling, and accessible treatment services.